ВИКОРИСТАННЯ ДОМЕН-НЕЗАЛЕЖНОГО ДІАЛОГОВОГО ВІКНА ДЛЯ ВИРІШЕННЯ ПРОБЛЕМ УПРАВЛІННЯ БАЗАМИ ДАНИХ - Chimir, Igor Alekseevich; Furtat, Yuriy Olegovich (Kamianets-Podilskyi National Ivan Ohiienko University, 2012)
Working with databases and forming queries to retrieve data requires knowledge of the stored data structure and access mechanisms. This can be a problem for unprofessional users. Means are to be developed to simplify this process, make it similar to the natural language use. in this article a domain-independent dialog-based problem solver is considered as one of such means.